PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN KONSUMEN PADA UD.WILLIAM KECAMATAN O’OU KABUPATEN NIAS SELATAN - Waruwu, Lilis Permata Kasih (Jurnal Ilmiah Mahasiswa Nias Selatan, 2024)
The iam of this research is to determine the effect of service quality on consumer satisfaction at UD. William, O’ou District, South Nias Regency. This research is quantitative research that is associative in nature. The population in this research is all consumer who make purchases at UD. William, O’ou District, South Nias Regency. The technique used in this research is incidental sampling technique with a sample of 40 respondents. The data source used in this research is primary data the. The data analysis technique used in the research is simple linear regression analysis. The research results show that service quality has a significant effect on consumer satisfaction. With the conclusion that service quality has a significant effect on consumer satisfaction. The researcher’s suggestion estimates that the management of UD. William improves and provides the same good quality service for every consumer who comes to buy and promises the Management UD. William to respond and respond to consumer well so that consumers are more comfortable when making purchases.